Recent advances in aqueous redox flow battery research. (1st December 2022) - Adeniran, Ayodeji; Bates, Alex; Schuppert, Nicholas; Menon, Ashwin; Park, Sam
Abstract: The aqueous redox flow battery (RFB) is a promising technology for grid energy storage, offering high energy efficiency, long life cycle, easy scalability, and the potential for extreme low cost. By correcting discrepancies in supply and demand, and solving the issue of intermittency, utilizing RFBs in grid energy storage can result in a levelized cost of energy for renewable energy sources that is competitive with non-renewable energy sources. With RFBs, the hope for the proliferation of renewable energy sources continues. In this review, recent advances in aqueous RFBs are explored, highlighting novel chemistries, configurations, and the current standard in operating current density and energy efficiency. This review contrasts the advantages and disadvantages of various aqueous RFB systems, while bringing attention to major challenges facing the technology. In addition, the current research trend and direction of RFBs are made apparent. Highlights: Recent advances in aqueous RFBs, highlighting novel chemistries, and configurations The current standard in operating current density and energy efficiency Contrasts the advantages and disadvantages of various aqueous RFB systems Bringing attention to major challenges facing the technology The current research trend and direction of RFBs is made apparent.